Management of acute bacterial meningitis in a limited resource setting: an Egyptian consensus model - Samy Zaky; Mohamed Elbadry; Maysaa A. Saeed; Hanaa Fathelbab; Fatma Abdelsalam; Mohammed Gamal Abdel-Hamid; Alshaimaa Eid; Asmaa Bakr; Amira Maher; Mona Mohammed Abdelrahman; Mohamed A. Metwally; Mahmoud Saad Berengy; et al. (The Egyptian Journal of Internal Medicine)
Abstract Acute bacterial meningitis (ABM) is an emerging disease with high morbidity and mortality. It is a globally serious disease and is considered endemic in Egypt, affecting all age groups and being common in low-standard and overcrowded areas. Early and appropriate antimicrobial therapy is crucial for suspected bacterial meningitis, even before the causative pathogen is identified. This is because definitive laboratory confirmation can take several days and may not always be successful. Those who do recover, especially if there was delayed appropriate intervention, can have permanent disabilities, such as brain damage, hearing loss, and learning disabilities. Rapid intervention in such cases is mandatory, which is not easy in countries with limited income due to weak capabilities and resources. Therefore, we are in dire need of making an Egyptian consensus that suits our country as a low-resource one, in order to facilitate and speed up the process of managing such cases. This consensus-based paper is under the supervision of the Egyptian Society of Fever comprising clinicians, microbiologists, epidemiologists, and public health representatives. They convened to assess the current situation and develop a new consensus on the management of ABM, taking into consideration the human and health potential of Egypt. All the experts who participated in writing and directing this conference belong to different Egyptian universities, and their main clinical interest was infectious diseases. Others work in fever hospitals that are affiliated with the Ministry of Health. They collaborated on the statements` writing, reviewing, and voting to reach the final version. Each statement was voted as strongly, moderately, or weekly recommended. Each statement should have a predefined score of 80% agreement to be accepted and reported in this consensus. Conclusion This Egyptian consensus model offers a feasible and context-specific approach to managing ABM, aiming to improve outcomes and reduce disparities in resource-limited settings.